The inside game in World Basketball. Comparison between European and NBA teams - Mavridis, G.; Tsamourtzis, E.; Karipidis, A.; Laios, A. (International Journal of Performance Analysis in Sport, 2009)
The purpose of the present study was to register the inside game and its determinants in both European and NBA teams. The sample consisted of 80 video-recorded European and NBA games. Elements analyzed were offensive tactics, the position of the pass maker, the kind of in pass, the frequency of players in post up position, the area of out pass. For the game analysis, the computer program used was the "Sportscout". The program used for the statistics analysis was the statistic packet SPSS and the non-parametric X² (chi square) distribution. The findings revealed that the dominant pass to centers in Europe was the bounce pass while in NBA, the overhead pass. In Europe, the center of a team had the biggest percentage of receiving a pass in post up position. On the other hand, in NBA, more players of the main team were found in post up position. In Europe, 72.7% of the control offence concerned the outside game while in NBA, only 55.0% of the offence concerned the outside game. The registration of the offensive behavior of high-level basketball teams could offer coaches a valuable aid at defining their aims in offence.